Race and sex differences in the measurement of risk for drug use - Gottfredson, Denise C. (Journal of quantitative criminology, 1997)
The study uses data from 2018 Black and White males and females and latent-variable structural equations techniques to examine group differences in the measurement of risk factors for substance use. First, the equivalence of measurement models for four demographic groups is examined separately for 12 risk factors and 2 measures of substance use. Then these 14 measures are correlated with five external criteria to assess measurement validity. Results imply that one measurement model fits the data for 11 of the 12 risk factors. For one risk factor (Peer Drug Modeling) and the two drug use scales, observed group differences in the factor loadings stemmed from differences in the distributions of a few drug-related items which were infrequently endorsed, especially by Black females. No meaningful group difference in the validity coefficients relating the scales to external criteria were observed. The results are optimistic for the study of race and sex differences in the correlates of substance use. But research on group differences in the prediction of rare behaviors should examine group differences in distributions which may effect measurement differently for different groups.